HUBUNGAN ANTARA DURASI MENGIKUTI LATIHAN YOGA DAN INDEKS MASSA TUBUH TERHADAP DAYA TAHAN KARDIORESPIRASI PADA PESERTA YOGA DEWASA MUDA DI KOTA DENPASAR - Putu Qonny Trisna Dewi; Ari Wibawa; Susy Purnawati (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACTCardiorespiratory endurance is the ability of heart, lungs, and blood capillary to take oxygen and distribute ontissue for metabolism process. Duration of exercise and body mass index is influence to cardiorespiratory endurance ofyoga practitioners. The method of this research is cross sectional analytic. This research is measure body mass indexand cardiorespiratory endurance with multi stage fitness test on thirty- seven sample. Analysis with Exact Fisher forrelationship between duration to cardiorespiratory endurance found the p value was 0.001 and relationship betweenbody mass index to cardiorespiratory endurance with the p value is 0.009. It’s means there are relationship betweenduration of yoga exercise and body mass index to cardiorespiratory endurance on young adult yoga practitioners inDenpasar City.Key word : Duration, Body Mass Index, Cardio respiratory Endurance, Yoga